OUTCOMES AND PROGNOSTIC FACTORS ASSOCIATED WITH CANINE SINONASAL TUMORS TREATED WITH CURATIVE INTENT CONE‐BASED STEREOTACTIC RADIOSURGERY (1999–2013). Issue 3 (15th February 2016) - Kubicek, Lyndsay; Milner, Rowan; An, Qi; Kow, Kelvin; Chang, Myron; Cooke, Kristen; Fox, Leslie; Farese, James; Bacon, Nicholas; Lurie, David
Abstract : Stereotactic radiosurgery (SRS) is a relatively new therapeutic option in veterinary oncology. The role of this modality has not been extensively evaluated for the use in canine nasal tumors. The objective of this retrospective, observational study was to describe the clinical outcome and prognostic factors associated with survival times in a sample of canine patients treated with SRS for sinonasal tumors. Fifty‐seven dogs with sinonasal tumors met inclusion criteria. Histologic diagnoses included sarcoma (SA) ( n = 9), carcinoma (CA) ( n = 40), osteosarcoma (OSA) ( n = 7), and round cell ( n = 1). Four of 57 cases were treated twice with SRS. For these, the median and mean doses delivered were 30Gy and 33Gy, respectively (range 18.75Gy–56Gy). Late effects occurred in 23 cases and ranged from grades I–III. The median overall survival time was 8.5 months. The median overall survival times in dogs with tumor type of CA, SA, and OSA were 10.4, 10.7, and 3.1 months, respectively. Dogs with the tumor type of OSA had shorter overall survival time than that in dogs with tumor type of CA and SA. Findings from this retrospective study indicated that SRS may be beneficial for canine patients with sinonasal tumors, however a controlled clinical trial would be needed to confirm this. Prospective studies are also needed to better define the role of SRS as palliative or curative, and to further investigate the risk of clinically significant toxicity.